Estimating the sources of stream water in snow dominated catchments of western Himalayas. (September 2021) - Lone, Altaf; Jeelani, Ghulam; Deshpande, R.D.; Padhya, Virendra
Highlights: This is the first detailed study in Sindh and Rambiara river catchments using stable water isotopes. The stable water isotopes of source waters showed marked spatial and temporal variations. Meteorology and topography of the region dominantly controls the isotopic composition. Meltwaters and groundwater were the major contributors to stream flow. Differential melting can have profound effect on stream discharge. Abstract: Snow and glaciers are important freshwater resources in the Himalayan catchments for all biological activities. However, under recent climate change, these resources are decreasing, thereby posing a serious threat to the future freshwater resources among the Himalayan catchments. Therefore, understanding the hydrological behaviour and sources of streamflow is necessary for better assessment, planning and management of these waters in the mountainous catchments. This study is based on the use of δ 18 O and d-excess to identify and estimate the different sources of streamflow in the western Himalayas. The isotopic composition of different source waters varied over space and time. These variabilities are attributed to the seasonal meteorological changes, precipitation form, differential melting of snowpacks and moistures sources. The vertical isotope gradients were observed between the sampling sites and the elevation of the basin. The results suggest that snow and snowpack dominantly (up to 55%) contribute to the streamflow during high flow period, while as groundwater maintains the flow in the streams during lean period and contributes up to 78%. The study provides the important insights about the understanding of spatio-temporal variability of different source waters contributing to runoff. In addition, the changing climate could have serious impact on the water resources of the region and thereby affecting the economic and social values of the downstream populations.